Modulus of Rupture and Modulus of Elasticity in Recycling FRP - Tri Nanda Citra Bangun; Nabila Rahmawati; Yopi Novita; Didin Komarudin; Mokhamad Dahri Iskandar; Deni Purnomo; Budhi Hascaryo Iskandar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Fiber Reinforced Plastic (FRP) material has been widely used as a ship construction alternative to wood. FRP has many advantages such as lightweight material, easy maintenance, weather resistance, economical price, and shorter production time. FRP ship production is weak from the waste factor produced, such as production residue during shipbuilding, ship molds, and FRP shipwrecks. FRP waste can impact the environment, economy, and human health. These impacts include soil pollution, microplastics, skin diseases, and human respiratory disorders. FRP material tends to be burned by many shipyards but still leaves waste in the form of dust. FRP material is difficult to decompose and takes a long time to melt. One strategic effort to minimize the impact of FRP is to recycle FRP. This study aims to reduce FRP waste by making composite boards from FRP waste. The method used was experimental, involving the making of 12 specimens and testing the density, MOR, and MOE. Based on the results of the density value test, the average value obtained follows the JIS A 5905-2003 reference. The MOR and MOE values for each specimen do not comply with the Indonesian Classification Bureau (BKI) standards. In the ANOVA test calculation, no significant differences were obtained for MOR and MOE.